2019
DOI: 10.1111/nep.13513
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine‐rich protein 61, a specific ultra‐early biomarker in kidney ischemia/reperfusion injury

Abstract: Aim: Studies have shown that cysteine-rich protein 61 (Cyr61) increased in the post-ischemic human kidney tissue. However, it is still unknown whether Cyr61 can be used as a biomarker in kidney ischemia/reperfusion (I/R) injury.Methods: Microarray data were collected from GSE58438 and GSE52004.The rat I/R model was established to evaluate the messenger RNA and protein expression of Cyr61, localization of Cyr61 by immunohistochemical and immunofluorescence staining, and changes in serum creatinine (Scr) at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…However, they all have a certain hysteresis and a lack of specificity, which are unable to identify the ultra-early stages of renal dysfunction. Therefore, ultra-early indicators are urgently needed for diagnosis of AKI to improve early prevention and treatment [ 36 ]. Our studies have shown that after renal IR injury, the level of Scr reaches the highest at 24 h, pathological damage is also the heaviest, accompanied by infiltration of inflammatory cells and activation of inflammatory cytokines (increased pro-inflammatory cytokines, decreased anti-inflammatory cytokines) [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, they all have a certain hysteresis and a lack of specificity, which are unable to identify the ultra-early stages of renal dysfunction. Therefore, ultra-early indicators are urgently needed for diagnosis of AKI to improve early prevention and treatment [ 36 ]. Our studies have shown that after renal IR injury, the level of Scr reaches the highest at 24 h, pathological damage is also the heaviest, accompanied by infiltration of inflammatory cells and activation of inflammatory cytokines (increased pro-inflammatory cytokines, decreased anti-inflammatory cytokines) [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considerable studies revealed that CCN1 is an immediate early gene product pertaining to the CCN family (CCN1/Ctgf/Nov family) and also a vascular regulatory factor of extracellular matrix cross-linking (Kleer, 2016;Wu et al, 2016;Yeger and Perbal, 2016). Intriguingly, CCN1 is a key protein in the transition from acute kidney injury (AKI) to CKD, and blockade of CCN1 can mitigate renal inflammation and fibrosis after ischemic reperfusion induced AKI (Lai et al, 2014;Li et al, 2019). Our previous study (Li et al, 2018) showed that as a hub gene, CCN1 overexpressed in CKD based on 373 CKD patient samples.…”
Section: Discussionmentioning
confidence: 99%
“…The homogenate was centrifuged at 10,000 g for 30 min at 4°C. 50 μg protein in mixture solution were separated with 10% SDS-PAGE and then transferred onto PVDF membranes of 0.45 μm (Millipore, Germany) incubated with 5% skimmed milk in phosphate-buffered saline at room temperature for 1 h (Li et al, 2019). After incubation with primary antibodies against and β-actin (Cell Signaling Technology, MA, United States) overnight at 4°C, the membrane was incubated with secondary antibodies after washing with PBS and Tween 20.…”
Section: Western Blottingmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have detected low levels of Cyr61 expression in the healthy adult kidney, but increased expression in ischemic renal tissue. It is also elevated in in lammatory states, suggesting it may be a potential biomarker for AKI [30,31]. Xu, et al found that Cyr 61 could protect tubular epithelial cells from apoptosis; however, its capability to detect AKI and when it is detected is still unknown [32].…”
Section: Il-18mentioning
confidence: 99%